Моделювання радіолокаційних систем у Matlab - Сєріков, А. О.; Свид, І. В. (ХНУРЕ, 2022)
The peculiarities of using the Matlab application program package for the study of radar systems as components of airspace control, control and surveillance of airspace are considered. It is shown that Matlab is a flexible and powerful package that allows for mathematical and simulation modeling of practical guidance.
Keywords: Matlab; радіолокаційна система; обробка сигналів